Aux origines d’Ibby-France - Francis Marcoin (Strenae)
An initial examination of the archives at the Paris branch of the CRILJ (Centre de recherche et d'information sur la littérature de jeunesse) filed at the University of Artois revealed historical links to the international organization IBBY (International Board on Books for Young People).This article will review, among other things, France’s importance within this organization, from the 1950s to the end of the 1980s, as well as joint brainstorming between the French branch of the IBBY and the CRILJ in the 1970s, when considering the creation of a children’s literature institute in France.